Kemampuan Air Kelapa Muda Sebagai Antimikroba Terhadap Bakteri Escherichia coli Penyebab Diare - Arif Mulyanto; Ikhsan Mujahid; Tyas Ulfah Khasanah (BIO-SITE |Biologi dan Sains Terapan, 2018)
Diarrhea is a circumstance when the body loses much fluid and electrolyte through feces. According to the data obtained by Ministry of Health of the Republic of Indonesia (2016), in 2015 there were 18 cases of healthemergency of diarrhea, spread over 11 provinces and 18 regencies/cities. There were 1.213 people who got the disease, 30 of them died. Partially, villagers treated diarrhea by drinking young coconut water. This research aimsto discover the effectiveness of several kinds of young coconut water as antimicrobials to bacteria that can causediarrhea (bacteria test) such as Escherichia coli. In this research the inhibitionof young coconut water sample toward above-mentioned bacteria was held. Besides, a phytochemical screeningtest was also conducted to find out the antimicrobial substances contained in young coconut water. The data of young coconut water antimicrobial testing toward Escherichia coli, wereanalyzed by employing analysis of varian (ANOVA) with F test on 95% confidence level. Data testing wasfollowed by Duncan test on 95% confidence level. Research results indicated that young coconut water had antimicrobial ability toward Escherichia coli. Based on the result ofphytochemical screening of the young coconut water (all treatments) it was only secondary metabolite tannins detected. All treatments (of the young coconut water) could inhibit tested bacteria. It is allegedly because thewater contained tannins. The water of green coconut (used as a traditional medicine) was an effective inhibitor of bacteria growth bacteri. On E. coli the inhibition zone diameter was 11,6 mm. Keywords: young coconut water, antimicrobial, bacteria, diarrhea